An Ultrasound Study of Cerebral Venous Drainage after Internal Jugular Vein Catheterization. (17th May 2012) - Vailati, Davide; Lamperti, Massimo; Subert, Matteo; Sommariva, Alberto
Abstract : Objectives . It has been advocated that internal jugular vein (IJV) cannulation in patients at risk for intracranial hypertension could impair cerebral venous return. Aim of this study was to demonstrate that ultrasound-guided IJV cannulation in elective neurosurgical patients is safe and does not impair cerebral venous return. Methods . IJV cross-sectional diameter and flow were measured using two-dimensional ultrasound and Doppler function bilaterally before and after IJV cannulation with the head supine and elevated at 30°. Results . Fifty patients with intracranial lesions at risk for intracranial hypertension were enrolled in this observational prospective study. IJV diameters before and after ultrasound-guided cannulation were not statistically different during supine or head-up position and the absolute variation of the venous flow revealed an average reduction of the venous flow after cannulation without a significant reduction of the venous flow rate after cannulation. Conclusions . Ultrasound-guided IJV cannulation in neurosurgical patients at risk for intracranial hypertension does not impair significantly jugular venous flow and indirectly cerebral venous return.